Association Between Combined Lifestyle Factors and Healthy Ageing in Chinese Adults: The Singapore Chinese Health Study. (1st February 2021) - Zhou, Yan-Feng; Song, Xing-Yue; Pan, Xiong-Fei; Feng, Lei; Luo, Nan; Yuan, Jian-Min; Pan, An; Koh, Woon-Puay
Abstract: Background: The aim of the study was to examine the relations of individual lifestyle factors and its composite score with healthy ageing among Chinese adults. Method: We included 14 159 participants aged 45–74 years at baseline from the Singapore Chinese Health Study, a population-based prospective cohort. A protective lifestyle score (0–5 scale) was calculated at baseline (1993–1998) and updated at the second follow-up visit (2006–2010) on the basis of optimal body mass index (18.5–22.9 kg/m 2 ), healthy diet (upper 40% of the Alternative Healthy Eating Index score), being physically active (≥2 h/wk of moderate activity or ≥0.5 h/wk of strenuous activity), nonsmoking (never smoking), and low-to-moderate alcohol drinking (>0 to ≤14 drinks/wk for men and >0 to ≤7 drinks/wk for women). Healthy ageing was assessed at the third follow-up visit (2014–2016) and was defined as absence of specific chronic diseases, absence of cognitive impairment and limitations in instrumental activities of daily living, good mental and overall self-perceived health, good physical functioning, and no function-limiting pain. Results: About 20.0% (2834) of the participants met the criteria of healthy ageing after a median follow-up of 20 years. Each 1-point increase in the protective lifestyle score computed at baseline and second follow-up visits was associated with higher likelihood of healthy ageing by 25% (95% CI: 20%–30%) and 24% (18%–29%), respectively. The population-attributable risk percent of adherence to 4–5 protective lifestyle factors was 34.3% (95% CI: 25.3%–42.3%) at baseline and 31.3% (23.0%–38.7%) at second follow-up visits for healthy ageing. In addition, positive increase in lifestyle scores from baseline to second follow-up visits was also significantly associated with a higher likelihood of healthy ageing with an odds ratio of 1.18 (95% CI: 1.12%–1.24%) for each increment in protective lifestyle score. Conclusions: Our findings confirmed that adopting healthy lifestyle factors, even after midlife, was associated with healthy ageing at old age.